Peningkatan Kemampuan Berbicara dalam Bahasa Inggris melalui Permainan Taboo Words - Dolli Rotua Sinaga; Emma Martina Br. Pakpahan; Jamaluddin Nasution; Kresna Ningsih Manik; Merry Susanty Br Tarigan (BADAN PENERBIT STIEPARI PRESS, 2025)
Mastery of English speaking skills is one of the main challenges for junior high school students. Lack of self-confidence and limited vocabulary are the main obstacles to learning. This activity aims to improve junior high school students' speaking skills through an educational game approach, namely Taboo Words. This game is designed to encourage students to describe an object, word, or concept without using taboo words. The activity was carried out for 60 minutes with junior high school students divided into small groups. The results of the activity showed an increase in active student participation, additional vocabulary, and the ability to describe in English creatively.